(untitled) (European Journal of Economics, Finance and Business Development, 2025)
Using the traditional method, calculations were carried out to determine the effect achieved as a result of implementing unified innovative technological processes for freight loading stations. It should be especially noted that the degree of distribution of the result or damage received between the parties between the railway transport and the client is important. These distribution levels indicate the need to use a method for determining economic efficiency based on the use of differentiated tariffs.